ANTESEDEN BRAND LOVE - Refiana Andriani; Nabila Azzahra Ramadhina; Fatik Rahayu (CV. Astina Mandiri, 2024)
This research aims to analyze the influence of brand personality on brand love, as well as its impact on purchase intention among marketplace users in Indonesia. Referring to relationship-based marketing theory, this research examines how brand personality builds emotional attachment (brand love), which in turn influences consumers' intentions to purchase products. Data was obtained through an online questionnaire involving 154 respondents and analyzed using the Structural Equation Model (SEM) method. The research results show that brand personality has a positive and significant influence on brand love, while brand love also contributes significantly to increasing purchase intention. This research provides managerial implications, namely the importance of companies developing branding strategies that are able to create deep emotional relationships with consumers to increase loyalty and competitiveness in the market.